Implementation of Problem Based Learning Model to improve students' critical thinking skills regarding HIV AIDS at SMK Tunas Bangsa Malang - Zulfah, Auliah Amina; Rohmah, Laila Nur; Ilmah, Nur Khozanah (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This classroom action research is motivated by students' suboptimal critical thinking skills. This study aims to determine the effect of the application of the Problem Based Learning (PBL) Learning Model on students' critical thinking skills in one of the Physical Education, Sports and Health materials regarding the Dangers of Transmission and Prevention of HIV/AIDS. The subjects of this study were 19 students of class XI SMK Tunas Bangsa Malang. The object of the study was the improvement of critical thinking attitudes using the Problem Based Learning (PBL) learning model. This study used gamification assistance in the ZEP Quiz to encourage active participation and student memory while working on the quiz/assessment. Data were collected through observation, critical thinking ability tests, and documentation. The results of the study showed that: (1) the PBL learning model can improve students' critical thinking skills through contextual problem solving in groups; (2) the use of ZEP Quiz gamification significantly encourages active participation, increases learning motivation, and strengthens students' memory of the material being studied; (3) there was an increase in the average value of students' critical thinking skills from cycle I by 67.25 to 82 in cycle II, and the percentage of students who achieved completion increased from 52.6% to 89.5%. Thus, the implementation of PBL assisted by ZEP Quiz has proven effective in increasing students' critical thinking skills on the material on the dangers of HIV/AIDS.